Does social information affect the settlement decisions of resident birds in their second breeding attempt? A case study of the Japanese Tit (Parus minor) - Xudong Li; Jiangping Yu; Dake Yin; Longru Jin; Keqin Zhang; Li Shen; Zheng Han; Haitao Wang (Avian Research, 2024)
Individuals may gather information about environmental conditions when deciding where to breed in order to maximize their lifetime fitness. They can obtain social information by observing conspecifics and heterospecifics with similar ecological needs. Many studies have shown that birds can rely on social information to select their nest sites. The location of active nests and the reproductive success of conspecifics and heterospecifics can provide accurate predictions about the quality of the breeding habitat. Some short-lived species can facultatively reproduce two and/or more times within a breeding season. However, few studies have focused on how multiple-brooding individuals select nest sites for their second breeding attempts. In this study, we use long-term data to test whether the Japanese Tit (Parus minor) can use social information from conspecifics and/or heterospecifics (the Eurasian Nuthatch Sitta europaea, the Daurian Redstart Phoenicurus auroreus and the Yellow-rumped Flycatcher Ficedula zanthopygia) to select a nest site for the second breeding attempt. Our results showed that the nest boxes occupied by tits on their second breeding attempt tended to be surrounded by more breeding conspecific nests, successful first nests of conspecifics, and fewer failed first nests of conspecifics than the nest boxes that remained unoccupied (the control group). However, the numbers of breeding heterospecific nests, successful heterospecific nests, and failed heterospecific nests did not differ between the nest boxes occupied by tits on their second breeding attempt and the unoccupied nest boxes. Furthermore, the tits with local successful breeding experience tended to choose areas with more successful first nests of conspecifics than those without successful breeding experience. Thus, we suggest that conspecifics' but not heterospecifics’ social information within the same breeding season is the major factor influencing the nest site selection of Japanese Tits during second breeding attempts.